Preparo e caracterização de hidrogéis injetáveis de galactomanana de Delonix regia oxidada e gelatina - Ramos, Everton Lucas de Lima (2019)
Injectable hydrogels are defined as a class of gels that can be prepared in situ by extruding their components directly to the desired location. Its components undergo a liquid → gel phase transition under physiological conditions due to chemical or physical crosslinking. Such hydrogels may be prepared from natural or synthetic polymers, and the use of those from natural sources is preferable for their similarity to some components of the natural extracellular matrix. Galactomannan is a heteropolysaccharide which due to its binding pattern can be oxidized by the periodate ion, giving rise to a derivative with two aldehyde groups for each monosaccharide unit, oxidized galactomannan (OXGM). Gelatin is a protein widely used for biomedical applications due to its biocompatibility and biodegradability. However, it finds limitations in its application associated with its low thermal stability at physiological temperature. Crosslinking with oxidized polysaccharides can be used as an alternative to overcome this problem by forming imine bonds, also known as Schiff's base (C = N). This work proposes the preparation and characterization of injectable hydrogels from Delonix regia OXGM and pigskin gelatin. Galactomannan was modified with different degrees of oxidation (10, 20, 50 and 70%). Oxidized derivatives were characterized by FTIR, GPC, TG and 1H NMR. The modification was confirmed by the appearance of a small band at 1723 cm-1 in the FTIR spectrum, which was attributed to the C = O bond stretch related to the presence of the aldehyde group. The oxidation process led to a progressive degradation of the galactomannan chain which resulted in a decrease in its peak molar mass. The oxidized derivatives showed a decrease in their thermal stability. NMR analysis showed the appearance of a series of signals in the region between 4.5 and 5.6 ppm, which are attributed to hemiacetallic structures. The hydrogels were prepared by combining OXGM (dissolved in PBS or 0.1 mol/L borax) with gelatin (dissolved in PBS) in the OXGM/Gelatin ratio of 1:1, 1:2 and 2:1. The combination of gelatin with OXGM led to an improvement in its thermal stability, thus showing that the crosslinking process was efficient. From the gelation time it could be determined that the ratios 1:1 and 1:2 were the most promising. The gelation times of the most promising formulations ranged from 5 to 53 minutes. The FTIR spectrum of the hydrogels showed a band at 1640 cm-1 which is associated with the C = N bond. Scanning electron microscopy has shown that hydrogels are formed by highly porous structures. Mechanical tests revealed a predominantly elastic behavior of hydrogels with values ranging from 9 to 36 kPa. The results obtained make these hydrogels possible candidates for future biomedical applications as agents for controlled drug release, cell encapsulation and/or space filling.